Óleos essenciais no controle da pinta bacteriana (pseudômonas syringae pv. tomato) do tomateiro: épocas de aplicação, concentração e indução de resistência - Silva, Érika Oliveira da (2015)
The bacterial speck has as etiologic agent the bacterium Pseudomonas syringae pv. tomato (Pst) and it is among the most important tomato diseases because it reduces the fruit size and quality by the appearance of spots. The losses caused by this disease result from the reduced productivity as a direct result of the symptoms, the cost of chemicals used as control strategy and its application to crops. The active ingredients that are contained in the products registered in Brazil for the control of bacterial speck are copper, streptomycin and oxytetracycline. However, several studies have shown the low efficacy of streptomycin and cupric products in tomato crops. Thus the essential oils appear as an alternative for the control of bacterial specks. As a consequence, this study was conducted with the following objectives: (i) to evaluate the in vitro effect of cinnamon (CA), citronella (CI), lemongrass (CL), clove (CR) , thyme (TO), eucalyptus (US), tea tree (ME), copaiba (CO) and lemon balm (EC) essential oils; (ii) evaluate the effect of these oils and the seasons of their application in the bacterial speck control (iii) evaluate the best concentration of the most promising essential oils for the bacterial speck control and (iv) evaluate the essential oil potential of citronella, lemon grass and acibenzolar-S-methyl in reducing bacterial specks and in the activation of some plant defense biochemical responses. In the concentration 1.0%, the essential oils of CA, CI, CL and EU promoted in vitro Pst growth inhibition. Regarding the influence of application times and disease control, the application of essential oils only once before inoculation presented higher control efficiency. The best treatments were the ASM and the essential oils of CI, CL and TO. Essential oils of CI 2.000 µL L-1 and CL 1.500 µL L-1, and ASM 0,2g L-1 were effective against tomato bacterial speck when applied only once seven days before inoculation. The essential oil of CI and acibenzolar-S-methyl conferred partial protection capacity in tomato plants challenged by P. syringae pv. tomato. They also promoted the increase in the total amount of phenol and the cell wall lignification.